Biological control of tomato bacterial wilt and apple fire blight through the induced resistance of azomycin derived from Streptomyces sp. JCK-8368 - Nguyen, Loan Thi Thanh; Park, Ae Ran; Im, Hye Won; Le, Ve Van; Nguyen, Hang T. T.; Le Dang, Quang; Hoa, Tran Thi Nhu; Yeo, Yu Jeong; Le, Ha Hang; Nguyen, Van Thi; Hwang, Inmin; Kim, Jin-Cheol (Frontiers in Plant Science, 2025)
Tomato bacterial wilt and apple fire blight, caused by Ralstonia solanacearum and Erwinia amylovora, respectively, are highly destructive diseases that threaten global agriculture productivity. Increasing resistance of these pathogens to conventional antibiotics and copper-based pesticides highlights the urgent need for sustainable, eco-friendly biocontrol alternatives. This study aimed to evaluate the biocontrol potential of the azomycin-producing Streptomyces sp. JCK-8368 (hereafter JCK-8368) against tomato bacterial wilt and apple fire blight, and to investigate its possible resistance-inducing mechanism. The culture filtrate (CF) of JCK-8368, containing azomycin, was applied to the plant at 1,000-fold (100 ng/mL), 500-fold (200 ng/mL), and 250-fold (400 ng/mL) dilutions via foliar spraying or soil drenching. Purified azomycin was tested at concentrations from 1 ng/mL to 1000 ng/mL. Disease severity and control efficacy were assessed, and expression of defense-related genes (PR1, PR2, PR3, and PR5) was also analyzed. Foliar spraying and soil drenching with JCK-8368 CF significantly reduced tomato bacterial wilt severity, with control efficacies of 52.22% (1000-fold), 11.11% (500-fold), and 35.55% (250-fold) in foliar application, 90.00%, 77.78%, and 52.22% in soil drenching, respectively. The reversed dose-response pattern in soil drenching indicated higher efficacy at lower concentrations. In apple fire blight control, soil drenching with CF at a 1,000-fold dilution achieved foliar spraying (78.38%) efficacy, exceeding soil drenching (50.88%). In particular, purified azomycin most effectively reduced tomato bacterial wilt at 100 ng/mL (57.14% efficacy) and showed a clear dose-dependent effect from 1 to 100 ng/mL. The plants treated with JCK-8368 CF and azomycin upregulated defense-related genes such as PR1, PR2, PR3, and PR5, suggesting systemically acquired resistance and pathogenesis-related defense pathways. This is the first report demonstrating the application of azomycin against plant bacterial diseases, showing that low concentrations of JCK-8368 and purified azomycin can effectively control tomato bacterial wilt and apple fire blight through induced resistance. Azomycin-producing Streptomyces sp. JCK-8368 offers a promising, sustainable alternative to chemical pesticides, warranting further field validation and formulation development for agricultural use.